DISPARITAS PEMBERIAN KREDIT BANK KONVENSIONAL DAN PEMBIAYAAN BANK SYARIAH TERHADAP UMKM: ANALISIS YURIDIS - Devica, Fitria Sri; Huda, M. Ikhwanul; Marzuki, A. Sofi (FACULTY OF ECONOMICS AND BUSINESS FLORES UNIVERSITY, 2025)
The purpose of this study is to determine the disparity between Sharia and Conventional Banks in conducting financing and credit to MSMEs. This kind of study uses statutory methods and normative legal theory. The findings of this study show that conventional banks and Islamic banks are different from one another. The first difference is seen in the fundamental ideas that each bank embraces. Conventional banks usually emphasize creditworthiness based on collateral or customer-owned collateral and use fixed or variable interest rate schemes. On the other hand, Islamic banks operate according to sharia law, which prohibits riba, or interest. The contract or agreement used by conventional and Islamic banks is the second difference. Islamic banks use musyarakah and mudharabah as forms of funding. However, conventional banks use leasing, factoring and credit contracts. The two banks' approach to risk management is the third difference. Islamic banks bear the risk, especially when funding items such as musyarakah and mudharabah. In Conventional banks, the customer bears all the business risk. Conventional banks charge late fees in the form of cumulative interest. The fourth difference relates to the way funds are raised and allocated. The objectives and funding strategies used by Islamic banks and conventional banks are very different. Since funds are allocated exclusively to activities that comply with Shariah regulations and halal values, the objects of financing in Islamic banks are often restricted. Islamic banks usually adopt a more individualized and partnership-focused approach to their customers. On the other hand, conventional banks do not have any restrictions on the object of funding, hence funds can be used for both halal and non-halal activities.